The Residual Medium and Long-term Cognitive Effects of Benzodiazepine Use: An Updated Meta-analysis. (13th December 2017) - Crowe, Simon F; Stranks, Elizabeth K
Abstract: Objective: This study presents an updated meta-analysis of the effects of benzodiazepines on cognitive functioning in long-term, current users of these agents, those who have recently withdrawn and on those who have successfully abstained following withdrawal. The study represents an update of the previous meta-analyses published by our group. Method: A comprehensive search of the computerized databases Medline and PsycINFO was undertaken to identify studies that assessed the cognitive effects of benzodiazepines published up to 28 November 2016 (the date of the last update). Nineteen studies (eight studies published since the previous meta-analyses and 11 studies included in the previous studies) were included. Results: The results of the analysis for current users revealed statistically significant, negative effects for the cognitive domains of working memory, processing speed, divided attention, visuoconstruction, recent memory, and expressive language. For those who had withdrawn and successfully abstained following withdrawal, deficits were observed for the domains of recent memory, processing speed, visuoconstruction, divided attention, working memory, and sustained attention. Conclusions: The results of the study are important in that they corroborate the mounting evidence that a range of neuropsychological functions are impaired as a result of long-term benzodiazepine use, and that these are likely to persist even following withdrawal. The findings highlight the residual neurocognitive compromise associated with long-term benzodiazepine therapy as well as the important clinical implications of these results.